Computers simplified - McFedries, Paul (Visual read less, learn more, 2007)
Here's the easiest guide ever to computers - a book that skips the long-winded explanations and shows you how things work. Full-color screen shots walk you through each step, and self-contained, two-page lessons make learning a snap. You'll learn to use different types of computers and software, create documents and use different programs, get online, start using e-mail, and manage your music and digital photos. A friendly character called Chip introduces each task, and sidebars offer real-world advice.
Keywords: Microcomputers; Electronic data processing